Determinants for the Decision of Delisting Companies from Stock Exchange: A Case Study of Tunisia, Egypt and Morocco - BILEL, Hadfi; KHAMMASSI, Ines (Theoretical and Practical Research in Economic Fields, 2024)
The Initial Public Offering (IPO) is considered a crucial step for a company, but its success is not guaranteed. This article aims to study the explanatory factors behind the delisting of a publicly traded company. To accomplish this, we have chosen a representative sample of 5 Tunisian companies, 5 Moroccan companies, and 10 Egyptian companies that were all delisted from the stock exchange between 2012 and 2021. Drawing on agency theory and signaling theory, we seek to identify the determinants that influence companies' delisting decisions. Three main findings are highlighted. This decision is positively influenced by: i) company-specific characteristics; ii) governance mechanisms; and iii) market situation. A theoretical and empirical approach is adopted to address this issue.